On the taxonomy of the Prabhasa / Zadadra generic complex with descriptions of two new genera and two new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini) - Dubatolov, Vladimir V.; Volynkin, Anton V.; Singh, Navneet; Joshi, Rahul; Černý, Karel (Zootaxa, 2021)
In the present paper, two new genera of the Prabhasa Moore, 1878 / Zadadra Moore, 1878 generic complex are described: Dentadra gen. nov. (Type species: Prabhasa flavicosta Moore, 1878) and Prabadra gen. nov. (Type species: Prabadra occidentalis sp. nov.). Additionally, two new species are described: Prabadra occidentalis sp. nov. (NE India and N Thailand) and Zadadra confusa sp. nov. (Nepal, NE India, Bhutan and W China). The new synonymy is established: Zadadra distorta Moore, 1872 = Zadadra neodistorta Joshi, Kirti & N. Singh, 2015, syn. nov. Two new combinations are established: Dentadra flavicosta (Moore, 1878), comb. nov. and Prabadra monastyrskii (Dubatolov, 2012), comb. nov. The lectotype is designated for Lithosia distorta Moore, 1872. Adults, male and female genitalia are illustrated. A checklist of the Prabhasa / Zadadra generic complex is provided.